PENGARUH APLIKASI KOMPOS DAN MIKORIZA ARBUSKULAR PADA TAILING TAMBANG EMAS TERHADAP PERTUMBUHAN DAN SERAPAN FOSFOR TANAMAN BUNGA MATAHARI - Izhar Ashofie; Budi Prasetya (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Tailings are waste (sludge) generated from various mining activities. Abundance of tailings can be a very serious problem in soils. One method that can be used to anticipate chemical hazard is phytoremediation using hyperaccumulator. Sunflower (Helianthus annuus L.) is one of the hyperaccumulator plants. In the other way, using compost to support macro and microelements for plants in phytoremediation activities can improve the physical and chemical of soil properties. Beside of using hyperaccumulator plants and compost, inoculation of arbuscular mycorrhiza (AM) can also be used to improve plant growth. The aim of this was to explore the effects of application of compost and mycorrhizal spores of Glomus sp. to gold mine tailing on sunflower growth, and P uptake. This study used a completely randomized design factorial consisting of two primary factors. The first factor was planting media composition (M) consisting of five levels and the second factor was the mycorrhizal spore numbers (S) consisting of three levels. The results showed that the composition of planting media (25% tailings : 75% compost) and the addition of 50 mycorrhiza spores increased plant height up to 45.67 cm (42.87%), and the leaves number 9.34 (72.97%), and able to increase P uptake 2.9 g plant-1 (45,79%).